Utilization of the Kahoot-it Application as a Learning Vehicle Based on Massive Open on Line Course (MOOC) during the Covid-19 Pandemic - Amin, Zulkifli; Dahnial, Irfan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This research shows that in the preparation stage, the implementation does the following things. (a) The implementer conducts socialization to the students of the Muhammadiyah University of North Sumatra through the Zoom media. (b) Implementers prepare questionnaires, attendance lists and other files for the purposes of activity reports. (c) Implementers re-register students who are actively enrolled in the class. (d) Executors prepare hardware devices in the form of computers/laptops, LCDs and so on. The approach in this research is qualitative (qualitative research). What is meant by qualitative research is to understand the phenomenon of what is experienced by the research subject holistically, and by means of description in the form of words and language, in a special natural context and by utilizing various scientific methods. From several different samples of students, there was a significant difference in the implementation of independent learning using MOOC-based Kahoot-it media. Therefore, these two different classes must be further improved with several methods that will be given later to students or later, so that the implementation of independent learning itself is carried out properly.